2024
DOI: 10.1007/s11082-023-06166-w
|View full text |Cite
|
Sign up to set email alerts
|

Inductively coupled plasma-mass spectrometry (ICP-MS) detection of trace metal contents of children cosmetics

Semiha Kopru,
Mustafa Soylak

Abstract: Consumption of cosmetic products in daily life in order to improve skin quality or appearance is becoming quite common. Over time, it may expose consumers to skin problems and effects caused by the absorption of chemical elements. Clean cosmetic production is important for our health. However, heavy metals can be found as impurities in raw materials or as by-products of the cosmetic production process. Women's ingestion and exposure to organic and inorganic contaminants in cosmetics through dermal absorption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
5

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 66 publications
1
3
5
Order By: Relevance
“…Among brands, the highest Pb concentration was observed in brand A, specifically in the sample A-4 coded, with a concentration of 171.200 µg g −1 which was 85-fold higher than the permissible limit set by BVL. In a recent study, the concentration of Pb was found in the range of 0.05–12.20 µg g −1 for child toy makeup, which was much lower than our findings (< LOQ–171.20 µg g −1 ) (Kopru & Soylak 2024 ). While the highest mean concentration of Pb was obtained at 363.889 µg g −1 in adult cosmetic research, in the current study, it was obtained at 81.71 µg g −1 (Mercan et al 2023 ).…”
Section: Resultscontrasting
confidence: 95%
See 3 more Smart Citations
“…Among brands, the highest Pb concentration was observed in brand A, specifically in the sample A-4 coded, with a concentration of 171.200 µg g −1 which was 85-fold higher than the permissible limit set by BVL. In a recent study, the concentration of Pb was found in the range of 0.05–12.20 µg g −1 for child toy makeup, which was much lower than our findings (< LOQ–171.20 µg g −1 ) (Kopru & Soylak 2024 ). While the highest mean concentration of Pb was obtained at 363.889 µg g −1 in adult cosmetic research, in the current study, it was obtained at 81.71 µg g −1 (Mercan et al 2023 ).…”
Section: Resultscontrasting
confidence: 95%
“…The current study showed that 2 in 10 brands were above the permissible limit set for Cd element; however, other brands were found < LOQ. According to the recent paper, the concentrations of Cd were determined with a concentration range < 0.01–0.25 µg g −1 , which is consistent with our study in toy makeup samples (Kopru & Soylak 2024 ). Similarly, trace amounts of Cd levels were reported in adult cosmetics as well (Mercan et al 2023 ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Bobaker et al [ 253 ] studied traditional plant-based beauty products marketed in Libya, respectively, henna (derived from the Lawsonia inermis ) and walnut tree bark (also known as souak—used both as a dental care product and as a popular enhancer for henna colors) and raised concerns about the potential presence of heavy metals such as Pb, Cd, and As in these cosmetics, posing health risks (due to their narrow safety margins) through skin absorption, and their accumulation in internal organs, which can result in toxicity. Before heavy metal analysis by ICP-MS, the samples were processed (walnut tree bark samples), oven-dried, and subjected to microwave-assisted digestion after the addition of a nitric acid (HNO 3 )/hydrogen peroxide (H 2 O 2 ) mixture [ 260 , 261 , 262 ]. ICP-MS analysis (Perkin Elmer SCIEX Elan 9000 ICP-MS, Perkin-Elmer SCIEX, Norwalk, CT, USA) of the samples revealed the presence of Pb, Cd, and As, with mean concentrations (Pb > Cd > As) having abnormally high standard deviations, which can be attributed to differences in product manufacturing, contamination levels, and the diverse sources of the products, influenced by varying climatic conditions.…”
Section: Ms Analysis Of Cosmetic Ingredientsmentioning
confidence: 99%